Standardization and evaluation of an Anti-ZIKV IgM ELISA assay for the serological diagnosis of zika virus infection - Sirikajornpan, Kanittha; Suntarattiwong, Piyarat; Suwanpakdee, Detchvijitr; Tabprasit, Sutchana; Buddhari, Darunee; Thaisomboonsuk, Butsaya; Klungthong, Chonticha; Poolpanichupatam, Yongyuth; Buathong, Rome; Srikiatkhachorn, Anon; Jones, Anthony; Fernandez, Stefan; et al. (My University, 2021)
Here, we describe the development of the in-house anti-Zika virus (ZIKV) IgM antibody capture ELISA (in-house ZIKV IgM ELISA) for the detection and diagnosis of acute ZIKV infections. We compared the in-house ZIKV IgM ELISA assay performance against two commercial kits, Euroimmun ZIKV IgM and InBios 2.0 ZIKV IgM ELISA. We tested the assays' ability to detect anti-ZIKV IgM using a well-defined serum sample panel. This panel included 80 ZIKV negative samples (20 negative, 20 found to be primary dengue virus [DENV][ infections, 20 secondary DENV infections, and 20 Japanese encephalitis virus [JEV] infections) and 67 ZIKV reverse transcriptase-polymerase chain reaction-positive acute serum samples. The OD values were calculated to enzyme immunoassay (EIA) unts by comparing them to weak positive controls. The results demonstrated the high sensitivity (88.06%) and specificity (90.00%) of our in-house ZIKV IgM ELISA and its 89.12% overall percentage agreement. The kappa values were deemed to be within excellent range and comparable to the InBios ZIKV IgM ELISA. Some cross-reactivity was observed among secondary DENV and JEV samples, and to a much lower extent, among primary DENV samples. These data indicate that our in-house ZIKV IgM ELISA is a reliable assay for the detection of anti-ZIKV IgM antibodies in serum.